The Involvement of Cx43 in JNK1/2-Mediated Endothelial Mechanotransduction and Human Plaque Progression - Tauchi, Miyuki; Oshita, Kensuke; Urschel, Katharina; Furtmair, Roman; Kühn, Constanze; Stumpfe, Florian; Botos, Balazs; Achenbach, Stephan; Dietel, Barbara (International Journal of Molecular Sciences, 2023)
Atherosclerotic lesions preferentially develop at bifurcations, characterized by non-uniform shear stress (SS). The aim of this study was to investigate SS-induced endothelial activation, focusing on stress-regulated mitogen-activated protein kinases (MAPK) and downstream signaling, and its relation to gap junction proteins, Connexins (Cxs). Human umbilical vein endothelial cells were exposed to flow (“mechanical stimulation”) and stimulated with TNF-α (“inflammatory stimulation”). Phosphorylated levels of MAPKs (c-Jun N-terminal kinase (JNK1/2), extracellular signal-regulated kinase (ERK), and p38 kinase (p38K)) were quantified by flow cytometry, showing the activation of JNK1/2 and ERK. THP-1 cell adhesion under non-uniform SS was suppressed by the inhibition of JNK1/2, not of ERK. Immunofluorescence staining and quantitative real-time PCR demonstrated an induction of c-Jun and c-Fos and of Cx43 in endothelial cells by non-uniform SS, and the latter was abolished by JNK1/2 inhibition. Furthermore, plaque inflammation was analyzed in human carotid plaques (n = 40) using immunohistochemistry and quanti-gene RNA-assays, revealing elevated Cx43+ cell counts in vulnerable compared to stable plaques. Cx43+ cell burden in the plaque shoulder correlated with intraplaque neovascularization and lipid core size, while an inverse correlation was observed with fibrous cap thickness. Our results constitute the first report that JNK1/2 mediates Cx43 mechanoinduction in endothelial cells by atheroprone shear stress and that Cx43 is expressed in human carotid plaques. The correlation of Cx43+ cell counts with markers of plaque vulnerability implies its contribution to plaque progression.
CRIS-Team Scopus Importer:2023-02-03
Keywords: atherogenesis; endothelial dysfunction; gap junctions; MAPK; mechanotransduction; shear stress